Пошаговое объяснение:
1)
(8х + 3) – (10х + 6) = 9;
8x + 3 - 10x - 6 = 9
-2x - 3 = 9
2x = -3 - 9
2x = -12
x = -12 : 2
x = -6
2)
2(7х - 7) = 7(2х - 3) + 7;
14x - 14 = 14x - 21 + 7
14x - 14 = 14x - 14
14x - 14x = 14 - 14
0 = 0
x є (-∞;∞)
3)
5(х - 12) = 6(х - 10) – х;
5x - 60 = 6x - 60 - x
5x - 60 = 5x - 60
5x - 5x = 60 - 60
0 = 0
x є (-∞;∞)
4)
7(4х - 1) = 6 – 2(3 – 14х);
28x - 7 = 6 - 6 + 28x
28x - 7 = 28x
28x - 28x = 7
0 ≠ 7
нет решений
5)
5,6 – 3(2 – 0,4х) = 0,4(4х - 1)
5,6 - 6 + 1,2x = 1,6x - 0,4
1,2x - 0,4 = 1,6x - 0,4
1,6x - 1,2x = 0,4 - 0,4
0,4x = 0
x = 0
3 целых 8.9 - у = 2 целых 7.9
у=3целых 8.9-2целых 7.9
у= 1 целая 1.9
б) (х - 3 целых 12.17) - 8 целых 9.17 = 4 целых 10.17
х-3целых 12.17= 8 целых 9.17 + 4 целых 10.17
х-3 целых 12.17=13 целых 2.17
х=3 целых 12.17+ 13 целых 2.17
х=16 целых 14.17